Fiber-based thermoelectrics for solid, portable, and wearable electronics - Shi, Xiao-Lei; Chen, Wen-Yi; Zhang, Ting; Zou, Jin; Chen, Zhi-Gang (Energy & environmental science, 2021)
With the growing demand for solid, portable, and wearable electronics, exploring recyclable and stable charging and cooling techniques is of significance. Fiber-based thermoelectrics, enabling sustainable power generation driven by the temperature difference or refrigeration without noise and freon, exhibit great potential for application in advanced electronics. In this work, we review significant advances in fiber-based thermoelectrics, including inorganic fibers, organic fibers, inorganic/organic hybrid fibers, and fiber-based fabrics and devices. The fundamentals, synthesis, characterizations, property evaluation, and applications of thermoelectric fibers are comprehensively discussed with carefully selected cases, and corresponding thermoelectric devices based on these advanced fibers are introduced for both power generation and refrigeration. Furthermore, we point out challenges and future directions toward the development of fiber-based thermoelectrics. This review comprehensively summarizes the recent progress of fiber-based thermoelectric materials and devices for solid, portable, and wearable electronics.